THE WORLD IS THE GREAT MIRROR OF CONSCIOUSNESS: REFLECTIONS ON THE QUANTUM IMPLICATIONS OF HEGEL'S ABSOLUTE IDEALISM - Bueno, Sinesio Ferraz [UNESP] (Univ Fed Reconcavo Bahia, Centro Formacao Professores, 2021)
In the field of quantum physics studies, Heisenberg's thought provokes very relevant reflections for an articulation between science and metaphysics, given the importance attributed to the subject in the collapse of the superposition between wave and particle. From an idealistic perspective, the importance given to the subject in the observation of quantum phenomena can be considered a stage of the development of consciousness within the scope of the phenomenology of Hegel's spirit. Quantum physics, under an idealistic perspective, represents a fundamental moment in the recognition and dialectical overcoming of the dualisms produced by the subject himself in his relationship with the world.
Keywords: Hegel; Metaphysics; Idealism; Quantum physics